2010
DOI: 10.1073/pnas.0910155107
|View full text |Cite
|
Sign up to set email alerts
|

Floral symmetry genes and the origin and maintenance of zygomorphy in a plant-pollinator mutualism

Abstract: The evolution of floral zygomorphy is an important innovation in flowering plants and is thought to arise principally from specialization on various insect pollinators. Floral morphology of neotropical Malpighiaceae is distinctive and highly conserved, especially with regard to symmetry, and is thought to be caused by selection by its oil-bee pollinators. We sought to characterize the genetic basis of floral zygomorphy in Malpighiaceae by investigating CYCLOIDEA2-like (CYC2-like) genes, which are required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
152
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(158 citation statements)
references
References 34 publications
4
152
1
1
Order By: Relevance
“…Although such reorientations appear to be rare across angiosperms (18), they may be more readily accomplished in Malpighiaceae, where two dorsal petal primordia are the norm early in development and the dorsal medial position of the mature banner petal appears to be achieved by a twisting of the flower stalk later in development (23). Indeed, recent developmental genetic studies (38)(39)(40) have shown that the expression of CYCLOIDEA2-like (CYC2-like) genes, which are responsible for establishing floral symmetry in a wide range of angiosperms, has been altered in Malpighiaceae. This finding provides a potential mechanistic basis for changes in floral symmetry coinciding with the loss of oil-bee pollinators (39), and shows that development per se does not significantly constrain changes in this trait.…”
Section: Resultsmentioning
confidence: 99%
“…Although such reorientations appear to be rare across angiosperms (18), they may be more readily accomplished in Malpighiaceae, where two dorsal petal primordia are the norm early in development and the dorsal medial position of the mature banner petal appears to be achieved by a twisting of the flower stalk later in development (23). Indeed, recent developmental genetic studies (38)(39)(40) have shown that the expression of CYCLOIDEA2-like (CYC2-like) genes, which are responsible for establishing floral symmetry in a wide range of angiosperms, has been altered in Malpighiaceae. This finding provides a potential mechanistic basis for changes in floral symmetry coinciding with the loss of oil-bee pollinators (39), and shows that development per se does not significantly constrain changes in this trait.…”
Section: Resultsmentioning
confidence: 99%
“…The CYC2 clade might have further experienced frequent duplications that gave birth to multiple copies of CYC2 genes in most members of zygomorphic clades within the Rosids and Asterids (Howarth and Donoghue, 2006). Of these, there is usually a pair of CYC2 clade genes involved in floral zygomorphy establishment redundantly, at least partially, with other copies having no or transient expression signals, such as CYC and DICH in snapdragon (Luo et al, 1996(Luo et al, , 1999, CYC1 and CYC2 in M. confertiflora (Hileman et al, 2003), CYC1 and CYC2 in L. japonicus (Feng et al, 2006;Wang et al, 2010), CYC1 and CYC2 in pea , CYC1A and CYC1B in Lupinus nanus (Fabaceae) (Citerne et al, 2006), CYC1C and CYC2A in O. dinghushanensis (Song et al, 2009), CYC2A and CYC2B in Byrsonima crassifolia (Malpighiaceae) (Zhang et al, 2010), and CYC2A and CYC2B in Lonicera (Caprifoliaceae) (Howarth et al, After expression initiation, CYC1C (blue box) and CYC1D (orange box) genes maintain expression throughout floral development via a double positive autoregulatory feedback loop by forming both homo-and heterodimers. The blue and orange circles represent the CYC1C and CYC1D proteins, and the blue and orange ovals represent the CYC binding sites found in the CYC1C and CYC1D promoters, respectively.…”
Section: Evolutionary Significance Of the Autoregulatory Loops In Cycmentioning
confidence: 99%
“…The dorsal identity function of CYC2 clade genes in patterning floral zygomorphy necessarily requires the coupling of at least two components (i.e., the expression maintenance by employing an autoregulatory loop and the expression location by evolving certain dorsal-specific cis-regulatory elements). Zygomorphy evolved independently several times from actinomorphic ancestors and is also frequently lost in the major zygomorphic lineages in angiosperms (Donoghue et al, 1998;Citerne et al, 2006;Zhou et al, 2008;Pang et al, 2010;Zhang et al, 2010). Therefore, it would be important to understand whether or how these secondary shifts are associated with a possible uncoupling of the two components, including a secondary change of the autoregulation loop and the regulatory alteration for CYC2 expression location, in the CYC2 gene regulatory pathway.…”
Section: Evolutionary Significance Of the Autoregulatory Loops In Cycmentioning
confidence: 99%
See 2 more Smart Citations